Are Human Resources Important to Support SDG’s in 2030? - Kusuma, Ajeng Nisa; Sari, Ratna Deli; Fadliah, Dina (Commercium : Journal of Business and Management, 2024)
Sustainable development must be implemented precisely in 2030 so that elements such as academics, stakeholders, the private sector and also the community must be able to implement the SDGs in that year. The SDGs here have 17 goals that must be implemented globally, but the problem that occurs here is that it is not as smooth as in implementing the SDGs considering that there are several phenomena that occur such as covid-19, gender issues and other problems. Human resources are expected to provide support to be able to implement the SDGs precisely in 2030. This study uses qualitative research based on literature studies. The results of this study explain that it turns out that the support from human resources for the SDGs can actually be said to be 50:50 because employees who are used as assets in this company can be fully responsible in supporting the SDGs considering that companies or organizations must have a vision and mission that must come first